ELECTRa Registry Outcome Score (EROS): validation in a single center population. (19th May 2022) - Segreti, L; Fiorentini, F; Giannotti Santoro, M; Barletta, V; Zucchelli, G; Di Cori, A; De Lucia, R; Canu, A; Viani, S; Paperini, L; Cellamaro, T; Soldati, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The ELECTRa Registry Outcome Score (EROS) was developed to identify patients at increased transvenous lead extraction (TLE) risk Purpose: Aim of the study is to explore the efficiency of EROS for stratifying patients undergoing TLE. Methods: We performed a retrospective analysis of 1293 patients who underwent to TLE in our center. We performed extraction procedures with manual traction or mechanical dilatation. We calculated EROS, and we divided patients into 3 groups depending on the EROS class. For this purpose, we made statistical analysis and comparison between EROS 1+2 vs. EROS 3 groups. We used an X2 for among-group comparisons or Fisher's exact test if the expected cell count was less than five. Results: Our analysis included 1293 patients. EROS-1 counted 726 patients (56, 1%), EROS-2 367 (28, 4%) patients and EROS-3 200 (15, 5%) patients. There was no statistical difference in peri-procedural death between EROS-1+2 and EROS-3 (0.18% vs 1.50%, p=0.134). Major complications (0.82% vs. 3.00%, p=0.014), minor complications (3.11% vs. 6.50%, p=0.019) and use of internal jugular approach (6.13% vs. 14.50%, p<0.001) was significantly higher in EROS 3 patients. Conclusion: EROS effectively separates patients at higher risk of complications. Use of internal jugular approach was significantly higher in EROS 3 patients.